Respon Pertumbuhan dan Produksi Tanaman Kailan (Brassica oleraceae L.) Varietas New Veg-Gin Akibat Pemberian Limbah Baglog dan Pupuk Organik Cair - Rudiyanto Rudiyanto; Darso Sugiono; Rika Agustini (Jurnal Ilmiah Wahana Pendidikan, 2023)
Baglog waste and Nasa organic liquid fertilizer (OLF) can be used as fertilizer to meet the nutritional needs of plants and increase the growth and yield of kailan plants. The purpose of this study was to obtain the best dose of baglog waste fertilizer and liquid organic fertilizer capable of increasing the growth and production of kailan plants (Brassica oleraceae L.) varieties of New Veg-gin. The method used was an experimental method with a single factor Randomized Block Design (RBD) consisting of 12 treatments that were repeated 3 times. The results showed that there was no noticeable effect of baglog waste and Nasa OLF aplications on plant height parameters, number of leaves, stem diameter, leaf area, and fresh weight of sample plants. However, there was a noticeable influence on the parameters of the volume of the roots. Treatments D and B gave higher average values of plant height, number of leaves, stem diameter, leaf area, and fresh weight of sample plants compared to other treatments. This shows that the provision of baglog waste and Nasa OLF independently is able to support the growth and development of kailan plants.